2018
DOI: 10.1155/2018/7570850
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Homocysteine Metabolism Genes Increase Keratin N-Homocysteinylation and Damage in Mice

Abstract: Genetic or nutritional deficiencies in homocysteine (Hcy) metabolism increase Hcy-thiolactone, which causes protein damage by forming isopetide bonds with lysine residues, generating N-Hcy-protein. In the present work, we studied the prevalence and genetic determinants of keratin damage caused by homocysteinylation. We found that in mammals and birds, 35 to 98% of Hcy was bound to hair keratin via amide or isopeptide bond (Hcy-keratin), while 2 to 65% was S-Hcy-keratin. A major fraction of hair Hcy-keratin (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…25 26 Consistently, CVDs are associated with Hcy-thiolactone and N-Hcy-protein, rather than t-Hcys, 27 and the Hcy-thiolactone/creatinine ratio is a significant predictor of acute myocardial infarction, independent of traditional risk factors and t-Hcy. 28 The serum paraoxonase (PON1) carried by high-density lipoprotein (HDL) protects blood proteins from N-homocysteinylation by hydrolysis of Hcy-thiolactone into Hcy. 29 PON1/HTase activity is associated with CAD risk.…”
Section: Introductionmentioning
confidence: 99%
“…25 26 Consistently, CVDs are associated with Hcy-thiolactone and N-Hcy-protein, rather than t-Hcys, 27 and the Hcy-thiolactone/creatinine ratio is a significant predictor of acute myocardial infarction, independent of traditional risk factors and t-Hcy. 28 The serum paraoxonase (PON1) carried by high-density lipoprotein (HDL) protects blood proteins from N-homocysteinylation by hydrolysis of Hcy-thiolactone into Hcy. 29 PON1/HTase activity is associated with CAD risk.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important cellular methylation processes is when betaine is involved in the remethylation of homocysteine to eliminate toxic metabolites [43]. Homocysteine is generated by deamination of methionine and is a toxic sulphur-containing intermediate product, and has various consequences for cells, such as oxidative stress, mitochondrial dysfunction, increased cytosolic calcium and protein damage [44], which all contribute to apoptosis [45]. Homocysteine generates ROS and inhibits the expression of antioxidant enzymes which might potentiate the toxic effects of ROS [45].…”
Section: Betainementioning
confidence: 99%
“…Our previous research has shown that carriers of FLG 2282del4 mutation, who were heterozygous for C677T polymorphism in the MTHFR gene (1p36.22, OMIM 607093), were 7 times as likely to develop ichthyosis as subjects with wild-type 677CC genotype [15]. It was also found that an elevated plasma homocysteine level impaired not only the metabolism of sulfur-containing amino acids, methionine, and cysteine, but also keratin molecules [16], [17], [18] that might exacerbate the effects of FLG null mutations. Every of single nucleotide polymorphisms (SNPs) of one-carbon metabolism genes -MTHFR C677T (rs1801133) and A1298C (rs1801131), MTR A2756G (rs1805087) and MTRR A66G (rs1801394) -are associated with plasma homocysteine level [19], [20].…”
Section: Introductionmentioning
confidence: 99%